2017
DOI: 10.1186/s12885-017-3504-1
|View full text |Cite
|
Sign up to set email alerts
|

A type I combi-targeting approach for the design of molecules with enhanced potency against BRCA1/2 mutant- and O6-methylguanine-DNA methyltransferase (mgmt)- expressing tumour cells

Abstract: BackgroundMutations of the DNA repair proteins BRCA1/2 are synthetically lethal with the DNA repair enzyme poly(ADP-ribose) polymerase (PARP), which when inhibited, leads to cell death due to the absence of compensatory DNA repair mechanism. The potency of PARP inhibitors has now been clinically proven. However, disappointingly, acquired resistance mediated by the reactivation of wild type BRCA1/2 has been reported. In order to improve their efficacy, trials are ongoing to explore their combinations with temoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The synthesis of non-isotopically labeled EG22 ( 8a ) was reported elsewhere [ 14 ]. As shown in Figure 1 , the first evidence of its instability was obtained by monitoring the appearance of a peak corresponding to the shielded proton ortho to the amino group of 4-amino-1,8-naphthalimide (ANI, 7a ) and the disappearance of a deshielded doublet of the aromatic ring of EG22 ( 8a ) in wet DMSO- d 6 at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The synthesis of non-isotopically labeled EG22 ( 8a ) was reported elsewhere [ 14 ]. As shown in Figure 1 , the first evidence of its instability was obtained by monitoring the appearance of a peak corresponding to the shielded proton ortho to the amino group of 4-amino-1,8-naphthalimide (ANI, 7a ) and the disappearance of a deshielded doublet of the aromatic ring of EG22 ( 8a ) in wet DMSO- d 6 at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, as shown in Figure 7 , using the Sulforhodamine B (SRB) growth inhibitory assay [ 23 ], we confirm that ZSM02 ( 9a ) and EG22 ( 8a ) exhibit similar growth inhibitory profiles. Further work on the mechanism of action of both molecules is reported elsewhere [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MGMT repairs methylated nucleobases in DNA by transferring methyl groups from O 6 -MG of DNA to cysteine residues in the active site of MGMT, resulting in MGMT inactivation and degradation [ 21 ]. Previous studies reported that MGMT was involved in DNA damage caused by the classical alkylating agent temozolomide (TMZ), as TMZ promotes formation of O 6 -methylguanine (O 6 MeG) and breakage of DNA strands [ 22 ]. However, our data showed that the MGMT expression was downregulated in autophagy-deficient liver cancer cells regardless of epirubicin, a non- alkylating agent, suggesting that the MGMT loss was not due to inactivation and degradation caused by repairing the DNA alkyl groups.…”
Section: Discussionmentioning
confidence: 99%